GERAKAN MAHASISWA FISIP UNIVERSITAS RIAU TAHUN 2017 - Rafli Suryadi; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Social movement was a part of social structure which consisted of typical pattern that manage social group and organization. Student as a well-educated elite group had an important part for building an history in a country. Based on ideological and intellectual prowess, student build a “movement of change” which commonly known as “student movement”. In this context, student have a significant part to developed a community awareness, political and social changes as the next step of the movement. Student social movement was mandatory to shield the truth and managed the social life in an environment and also government exerted in a certain country. The aim of this study was to acknowledged the faculty of social and political sciences Riau University student movement in 2017 and also to determine some factors that influenced it. This was a descriptive study with qualitative analytics methods. This study took part in faculty of social and political sciences Riau University based on the concern of unhappiness in student community for their study facility and environment. The writer also had an adequate knowledge for the situation and condition in the place to made a more suitable for analysed of phenomenon in the environment. Sample collection had been done by observational, interview and documentation by location. The data analysis was done by qualitative analysis. We found that the faculty of social and political sciences Riau University student movement in 2017 had several methods to describe their interest. Student movement had a “softer approached” with audience that followed by peaceful demonstration or vice versa. Student movement also encompassed the journalistic media to improve student awareness for their campus issues. It was happened as a response from the limitation of transparency in financial management of their campus which made a student charge.Keyword: Campus, Student, Demonstrate